(untitled) (International Seven Journal of Multidisciplinary, 2023)
Studies have shown that colors have a direct influence on the thermal behavior of surfaces, a factor that should always be considered in any area, especially construction. Based on these factors, this project is part of the thermal energy context and its main objective is to evaluate the interference of colors on the thermal performance of environments. To this end, four prototype houses were built and covered with fiber cement tiles in different colors (white, brown, red and black). A glass of water was placed in each prototype and used to submerge the infrared thermometer to measure temperatures, twice a day for four days. The data was collected, validated and organized into tables and graphs. After analyzing the data, it was noted that the environment covered by the black roof tile had higher temperatures on all measurement days at all times, followed by the brown, red and white colors, converging with the literature studied. Finally, it can be concluded that the color of the roof has a great influence on the temperature of the internal environment and should be taken into account when designing an architectural project.